Steel Management on Two Continents - Harbison, Frederick (Relations industrielles / Industrial Relations, 1955)
SummaryA cross national analysis of managerial organization and supervisory personal in order to highlight some of the similarities and contrasts in two industrial societies, U.S.A. and Germany. The following pilot study is limited to operating management and supervision of two steel works.